Bimodal distribution and set point HBV DNA viral loads in chronic infection: retrospective analysis of cohorts from the UK and South Africa - Downs, L; Matthews, P; Vawda, S; Bester, A; Lythgoe, K; Wang, T; McNaughton, A; Smith, D; Maponga, T; Freeman, O; Varnai, K; Fraser, C; et al. (F1000Research, 2020)
Hepatitis B virus (HBV) DNA viral loads (VL) show wide variation between individuals with chronic hepatitis B (CHB) infection, and are used to determine treatment eligibility. There are few refined descriptions of VL distribution in CHB, and limited understanding of the biology that underpins these patterns. We set out to describe the VL distribution in independent cohorts from the UK and South Africa, to identify associated host characteristics, and to compare with VL in HIV-1 and hepatitis C (HCV) infection. We show the presence of a 'set-point' in chronic HBV infection and report significant differences in the viral load distribution of HBV when compared to HIV and HCV including a bimodal distribution of viral loads and a much lower median HBV viral load.